Reform of Working Hours Regulations for Medical Specialist Education Programs Towards Balance in Education and Service - Hutagalung, Tiur Hasmida; Fakrulloh, Zudan Arief (Journal Of Social Science (JoSS), 2024)
Regulations on working hours for Medical Specialist Education Program (PPDS) participants in Indonesia play an important role in maintaining a balance between education and health services. However, legal loopholes and lack of supervision have led to many PPDS participants being forced to work beyond the prescribed limits, which negatively affects their physical and mental health. This study aims to analyze existing regulations related to PPDS working hours, identify legal loopholes that affect the welfare of participants, and provide recommendations for regulatory improvements. The method used in this research is a normative legal research method with a legislative and conceptual approach. The data used are secondary sources, including relevant laws, legal journals, and official government documents. The results show that although there are regulations governing working hours, their implementation is often inconsistent in the field. Many PPDS participants reported working hours exceeding 80 hours per week, especially in emergency situations. This finding indicates the need for legal reform to create a better system. In conclusion, regulatory reforms regarding working hours for PPDS participants are urgently needed to ensure the welfare of participants and the quality of health services. Recommendations for improvement include stricter enforcement of working hour limits, improved supervision systems, and active collaboration with the Ministry of Health.